2014
DOI: 10.3389/fnhum.2014.00071
|View full text |Cite
|
Sign up to set email alerts
|

Kinesthetic and vestibular information modulate alpha activity during spatial navigation: a mobile EEG study

Abstract: In everyday life, spatial navigation involving locomotion provides congruent visual, vestibular, and kinesthetic information that need to be integrated. Yet, previous studies on human brain activity during navigation focus on stationary setups, neglecting vestibular and kinesthetic feedback. The aim of our work is to uncover the influence of those sensory modalities on cortical processing. We developed a fully immersive virtual reality setup combined with high-density mobile electroencephalography (EEG). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 42 publications
(82 reference statements)
9
75
0
2
Order By: Relevance
“…However, we already know that the act of moving is central to navigation. For example Ehinger et al (2014) have shown that the integration of vestibular and kinesthetic information (provided through the navigation of the physical body in the environment) modulates brain activity in the alpha frequency band. These findings demonstrate that sensory and vestibular feedback are essential parts of spatial navigation that are neglected in lab-based navigation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, we already know that the act of moving is central to navigation. For example Ehinger et al (2014) have shown that the integration of vestibular and kinesthetic information (provided through the navigation of the physical body in the environment) modulates brain activity in the alpha frequency band. These findings demonstrate that sensory and vestibular feedback are essential parts of spatial navigation that are neglected in lab-based navigation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As the SMC theory states the importance of action for developing new SMCs a possible control would also be a passive training condition. In fact, a recent study on integration of kinesthetic and vestibular information by EEG in a virtual reality environment reported significant differences in cortical processing between active and passive conditions [121]. To apply such techniques in the context of sensory augmentation is an important next step.…”
Section: Discussionmentioning
confidence: 99%
“…the sound channel of the movie). Finally, signals from accelerometers and other motion sensors could help to account for the head and body movements that characterize visual exploration behavior outside of the laboratory (Ehinger et al, 2014;Gramann, Jung, Ferris, Lin, & Makeig, 2014).…”
Section: Improving the Understanding Of Fixation-related Brain Activitymentioning
confidence: 99%